Alticola macrotis Radde 1862 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Alticola macrotis Radde, 1862. Reise in den Suden von Ost-Sibierien, 1:196, Die Saugethierfauna im Suden von Ost-Sibirien. Besobrasoff, St. Petersburg. TYPE LOCALITY: U.S. S. R., R.S.F.S. R., S. Krasnoyarsk. Krai, E. Sayan Mtns. DISTRIBUTION: Sayan and Altai Mtns.; mountains S.E. of Lake Baikal and head of Shilka River (U.S. S.R.); Khangai Mtns. (Mongolia). COMMENT: See comment under Eothenomys lemminus. ISIS NUMBER: 5301410008068002001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 4), pp. 477-504 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 479, DOI: 10.5281/zenodo.7353034